Estado, ciência e política na Primeira República: a desqualificação dos pobres - Patto, Maria Helena Souza (Estudos Avançados, 1999)
STARTING FROM THE RECONSTITUTION of the economic, politic and social aspects of the First Republic in Brazil, in this report is questioned the direct and wholesome transposition to this Brazilian historical period of Foucaults view of the European societies from the turning of the eighteenth century. Carrying on the authoritarian tradition of the social classes relationships in this country, the first republican period relied on a despotic and violent police, more than on the subtle disciplinarian medical ways, in trying to control the "urban chaos". If science had any role on this practice, it was mainly the result of the dissemination of a negative racist social representation of the members of the underprivileged classes.